Estudo químico de Phytophthora Nicotianae e sua influência no perfil químico de plântulas de Citrus Sinensis - Rabêlo, Waléria Ferreira (Universidade Federal de São Carlos, 2018)
“PHYTOPHTHORA NICOTIANAE CHEMICAL STUDY AND ITS INFLUENCE ON THE CHEMICAL PROFILE OF CITRUS SISENSIS SEEDLINGS.” The present work describes the study of the variation of the citrus chemical profile after the inoculation of the omicetto "Phytophthora nicotianae", responsible for citrus gomose disease, which is one of the diseases that is causing damages in Brazilian citriculture. For this, "P.nicotianae" was inoculated in "Valencia" seedlings [Citrus sinensis (L.) Osbeck] grafted on "Citrumelo Swingle" (Citrus paradisi x Poncirus trifoliata) and Sunki Tropical Tangerine [Citrus Sunki Hort. ex Tan], where it was evaluated chemical profile of the major secondary metabolites through the development of analytical methods such as HPLC-UV, LC-MS / MS, CG / MS and UHPLC-MS / MS with chemometric tools. These chemometric tools applied to the data obtained in the UHPLC-MS / MS studies allowed discriminating the infected plants with the omicetto of healthy plants, as well as the characterization of the compounds that contribute most to this differentiation. When analyzing the chemical profile variation of the citrus studied by the UHPLC-MS / MS technique it was possible to detect the variation mainly of some coumarins in the roots and lower stem. Glycosylated flavonoids in the leaves the gomose infected seedlings and the healthy ones indicating that these compounds may be involved in the plant defense mechanism, and may be considered a phytoanticipal. In the methodology used for the study of volatile biomarkers in the HS / GC-MS, it was possible to observe variations and the main volatile markers for the studied matrices, was D-limonene and guaiacol in stems and leaves, matrices inoculated with the pathogen causing the disease gomose of citrus. In addition, the chemical study of the oomiceto in some culture was done, in addition to comparisons of mycelial growth with the objective of obtaining standard substances, which resulted in the isolation of lesser known secondary metabolites of the anthron class.
Phytophthora Nicotianae chemical study and its influence on the chemical profile of citrus Sisensis Seedlings
Keywords: Phytophthora nicotianae; Citrus sinensis; Tangerina Sunki Tropical; Citrumelo Swingle; Metabolômica; Oomiceto; Perfil Químico; Cumarinas; Flavonoides; Tropical Sunki tangerine; Omicetto; Profile chemical; CIENCIAS EXATAS E DA TERRA::QUIMICA